DEPENDENSI DALAM MODEL RESIKO INDIVIDUAL UNTUK ASURANSI JIWA KELOMPOK - Getut Pramesti; Sri Haryatmi Kartiko (Journal of Mathematics and Mathematics Education, 2011)
ABSTRACT: The  risk  dependence  of  an  insurance  portfolio  in  a  group  life  insurance  can  be  described  as  the individual risk model. It is used in modeling the claim distribution of insurance contracts over a fixed period  of  time.  The  distribution  computation  is  conducted  with  direct  calculation  throught  n convolution of individual claim distribution. We discuss the impact of the risk dependence on the net value of the stop–loss premium. A third risk factor in the dependence risk model is also introduced.Key words : The risk dependence, group life insurance, individual risk model, claim, the net value of the stop-loss premium.